Comparative study of design base shear of building using IS standard and ASCE standard - Shambharkar, Rohit R.; Pawade, P. Y.; Deshmukh, Aditya (AIP conference proceedings, 2024)
Seismic analysis is essential when constructing buildings that are subject to seismic shaking to ensure that the structure is stable and fit for purpose in the event of an earthquake. This process is called seismic design. Every country in the world has seismic regulations that must be followed when planning, designing, and constructing structures. Seismic standards help minimize loss of life and property and improve the stability of buildings to withstand the effects of earthquakes. The purpose of this study is to determine correlations between parameters like soil type, time period, zone factors, base shear, etc. used for designing tall buildings using different international building codes. Two well-known structural codes are used that are Indian Standard (IS1893–2016) and American Standard (ASCE7). The performance of any structure depends on the following criteria: lateral shaking criteria, thermal movement, and interaction between structure and architecture. The primary concern is the stability and reliability of the entire structure and its components, as well as their ability to withstand loads and applied forces. It is convenient to design a building considering earthquake resistance rather than earthquake-proof. Of course, the first approach can lead to disaster, and the second approach is too costly. Therefore, the design philosophy should be somewhere between these two extremes.